From the topological spin-Hall effect to the non-Hermitian skin effect in an elliptical micropillar chain - Mandal, Subhaskar (2023)
The topological spin-Hall effect causes different spins to propagate in opposite directions based on Hermitian physics. The non-Hermitian skin effect causes the localization of a large number of modes of a system at its edges. Here we propose a system based on exciton-polariton elliptical micropillars hosting both the effects. The polarization splitting of the elliptical micropillars gives rise to the topological spin-Hall effect in a one dimensional lattice. When a circularly polarized external incoherent laser is used to imbalance effective decay rates of the different spin polarizations, the system transits to a non-Hermitian regime showing the skin effect. These effects have implications for robust polariton transport as well as the deterministic formation of multiply charged vortices and persistent currents.